Réponses

2014-02-17T16:53:20+01:00
A=(+8)+(-4)-(+5)-(-7)
8-4-5+7
6

B=(-14)-(-23)+(+9)-(+21)
-14+23+9-21
-3

C=(-8)-(+7)-(-18)-(+3)
-8-7+18-3
0

 A=(-1.7)+(+3.5)-(-2.3)
-1.7+3.5+2.3
4.1

B=(-7.8)-(-11.4)-(+4.5)
-7.8+11.4-4.5
-0.9

C=(+5.6)+(-8.4)-(+3.8)-(-4.2)
5.6-8.4-3.8+4.2
-2.4

+ +=+
- + =-
+ -=-
- - +
2014-02-17T16:56:43+01:00
A=(+8)+(-4)-(+5)-(-7)
A = 4 - (+5) - (-7)
A = -1 + 7
A = 6

B=(-14)-(-23)+(+9)-(+21)
B = (-14) + (23) + (+9) - (+21)
B = 9 + 9 - (+21)
B = 18 - 21
B = -3

C=(-8)-(+7)-(-18)-(+3)  
C = -15 - (-18) - (+3)
C = -15 + 18 - 3
C = 3 - 3
C = 0

A=(-1.7)+(+3.5)-(-2.3)
A = 1,8 + 2,3
A = 4,1

B=(-7.8)-(-11.4)-(+4.5)
B = -7,8 + 11,4 - 4,5
B = 3,6 - 4,5
B = -0,9

C=(+5.6)+(-8.4)-(+3.8)-(-4.2)

C = 5,6 - 8,4 - 3,8 + 4,2
C = -2,8 - 3,8 + 4,2
C = -6,6 + 4,2
C = -2,4